2017
DOI: 10.1063/1.4984776
|View full text |Cite
|
Sign up to set email alerts
|

Small amplitude double layers in a warm electronegative plasma with trapped kappa distributed electrons

Abstract: We employ quasipotential analysis to derive the Sagdeev potential which accounts for the effect of electron trapping in a warm electronegative plasma with κ-distributed electrons. The trapped electron density is truncated to some finite order of the electrostatic potential Φ. This consequently leads to an extended KdV equation which gives rise to small amplitude double layers (SIADLs). The effects of various plasma parameters, e.g., superthermality index, the electron trapping efficiency, the mass ratio of neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Similarly by ignoring the trapping effect of electrons and for r = 0 and q → κ + 1, we get the Burger equations (39) of [45] for free kappa distributed electrons and positron. Again for r = 0 and q → κ + 1, we get the modified Burger equation (30) of [46] in the presence of kappa distributed trapped electrons and kappa distributed free positron. The stationary solitary solution of equation (39) can be obtained by introducing the following traveling variable…”
Section: Burgers' Equation In the Presence Of Trapped Electronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly by ignoring the trapping effect of electrons and for r = 0 and q → κ + 1, we get the Burger equations (39) of [45] for free kappa distributed electrons and positron. Again for r = 0 and q → κ + 1, we get the modified Burger equation (30) of [46] in the presence of kappa distributed trapped electrons and kappa distributed free positron. The stationary solitary solution of equation (39) can be obtained by introducing the following traveling variable…”
Section: Burgers' Equation In the Presence Of Trapped Electronsmentioning
confidence: 99%
“…All physical quantities appearing in equations (10)−( 15), ( 17) and (18), are expanded as power series in 'ε' about their equilibrium values as Now incorporating the stretched coordinates from equation (45) and perturbed quantities expanded in power series of ε from equation (46) into the basic set of fluid equations ( 10)-( 14), ( 17) and ( 18), we obtain a set of equations by comparing different powers of ε. A nonlinear evaluation equation is obtained by following the same procedure used for the derivation of equation ( 39) as…”
Section: Burgers' Equation In the Presence Of Free Electronsmentioning
confidence: 99%
“…Using the reductive perturbation technique, Hafez et al [34] have derived the modified Kadomtsev-Petviashivili (mKP) equation to elucidate the effect of electron trapping on the features of the nonlinear oblique propagation of ion-acoustic solitary excitations in unmagnetized e-p-i plasmas. Shan et al [35] have investigated the basic characteristics of the small but finite amplitude of ion-acoustic double layers and solitons in a collisionless, unmagnetized plasma containing warm adiabatic inertial ions, cold inertial positron, and trapped noninertial electrons modelled by the Kappa trapped distribution function. Chowdhury et al [36] have used the reductive perturbation technique to derive a forced Korteweg-de Vrieslike Schamel equation and study the influence of an external periodic perturbation on the localized solitary pulses in an unmagnetized plasma with kappa-distributed trapped electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the ion-acoustic DL has been a topic of significant interest because of its relevance in cosmic applications, [14][15][16][17] confinement of plasma in tandem mirror devices, [18] ion heating in linear turbulence heating devices, [19] etc. Using the pseudo-potential approach and reductive perturbation method, several authors [20][21][22][23] have studied ion-acoustic DLs in different plasma systems. Electronegative plasmas, i.e., plasmas containing an appreciable amount of negative ions, are found in plasma processing reactors, [24] neutral beam sources, [25] the cometary comae, [26] and the upper region of Titan's, [27] etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the ion-acoustic wave phase velocity, in different concentration of negative and positive ions, decreases as the non-extensive parameter q increases. Shaukat and Nadia [29] investigated small amplitude DLs in a warm electronegative plasma with trapped kappa distributed electrons. They have found that the small amplitude ion-acoustic DLs are significantly modified by the variation of various parameters such as the electron trapping efficiency and the ratio of the mass of negative ion to positive ion.…”
Section: Introductionmentioning
confidence: 99%